Corrigendum to the author’s name of Teguh WijayaMulya (2006 - 2016) - Teguh WijayaMulya (ANIMA Indonesian Psychological Journal, 2018)
Corrigendum to the author’s name of Teguh WijayaMulya (2006 - 2016)